The Grooming used in infographic of Yaqeen News Agency on Iraqi issues - An analytical study Specialization (media-journalism) - Assistant teacher Haseeb Khalaf Muhemed (Genius Journals, 2024)
This study aims to know the types of grooming used in the infographics of Yaqeen News Agency about the issues of Iraq and to know their contents and the forms of infographics used in them and the most prominent use among the grooming used in the infographics, as the study comes to the importance of infographics in the media and the service it provides in simplifying information and data to the public in a clear and easy way. The researcher used in this study the survey method that is concerned with surveying the phenomenon that is the subject of the study, and the problem of the study revolved around the following question (What are the uses used in the infographics of Yaqeen News Agency about the issues of Iraq?), and the researcher reached the following results: The diversity of grooming used in 1- the infographics of Yaqeen News in terms of content, as the economic infographic emerged as the top of the contents, followed by the political, security and social contents. 2- The mental, emotional and intimidating grooming emerged, through which the agency used more than one idea to attract and excite the public. 3- The diversity of grooming used in infographics in terms of form, as the analysis results showed that statistical infographics are the most interesting for Yaqeen News Agency.
Keywords: Grooming; infographic; Iraqi issues